An electron microscopic study of the glomerular epithelial detachment - SUZUKI, YASUHITO; SHIMOTORI, TAKASHI; ISHIYAMA, TAKESHI; ARAKAWA, MASAAKI; FUKAGAWA, MITSUTOSHI; KOUDA, YUTAKA (Nihon Jinzo Gakkai shi, 1985)
Different types of the glomerular epithelial detachment have been reported in various glomerular diseases. Kidney biopsy specimens from 116 patients were investigated by electron microscopy with special attention to this lesion . The epithelial detachment was classified into 4 types: (1) glomerular basement membrane (GBM) denudation (Type I), (2) epithelial desquamation (Type II), (3) subepithelial protrusion (Type III), and (4) subepithelial expansion (Type IV). Type I was observed in almost all kinds of glomerular diseases, particularly associated with nephrotic syndrome. This lesion, however, was noticed in the cases showing only hema tuna. Type II was accompanied by either GBM abnormalities including attenuation, wrinkling, irregular thickening, splintering, and amyloid deposition, or subepithelial widening with or without electron dense deposits . Type III was seen mostly in the patients with massive proteinuria. It seemed to be the early lesion of segmental sclerosis. Type IV was the most advanced epithelial detachment seen in the sclerotic glomerular tufts. The typical lesion was observed in focal glomerular sclerosis, although it is not pathognomonic. Some of the epithelial detachment such as Type III or IV may possibly develope into segmental glomerular sclerosis, However other unknown factors may also be concerned in this process, since these detachments are commonly seen in various glomerular diseases. In conclusion, the severity of epithelial detachment is correlated with the degree of glomerular damage and proteinuria.